Effect of nitrogen fertilization and microbial preparations on potato yielding - M. Kołodziejczyk (Plant, Soil and Environment, 2014)
The effect of nitrogen fertilization and microbial preparations on yielding and development of potato tuber yield components were assessed in field experiments conducted under soil conditions of Luvic Chernozem. The factors of the experiment were nitrogen fertilization levels: 0, 60, 120 and 180 kg N/ha and the following preparations: BactoFil B10, effective microorganisms and UGmax soil fertilizer. Nitrogen fertilization caused a significant increase in marketable yield of potato tubers. Yield increments on individual fertilizer treatments ranged from 66% to 140%. An evident effect of this factor was also visible regarding the yield components values. Increase in the number of main stems per 1 m2 under the influence of growing nitrogen doses occurred from the fertilization level 120 kg N/ha, whereas the number of tubers per 1 stem increased only to the level of 60 kg N/ha. Each nitrogen dose applied within the range to 180 kg N/ha caused a marked increase in an average tuber weight. Conducted investigations demonstrated an unfavourable effect of microbial preparations on the marketable crop yield of tubers and formation of yield components. On the objects where microbial preparations were applied, the marketable yield was lower by 1.5 to 2.3 t/ha than in the control. Analysis of linear regression revealed occurrence of significant dependencies between the total tuber yield and the values of individual yield components. The relationships were the most visible for an average tuber weight formation as evidenced by the value of coefficient of determination (R2 = 0.983).